Mice lacking α4 nicotinic acetylcholine receptors are protected against alcohol‐associated liver injury. (3rd July 2022) - Watson, Walter H.; Ritzenthaler, Jeffrey D.; Torres‐Gonzalez, Edilson; Arteel, Gavin E.; Roman, Jesse
Abstract: Background: Chronic heavy alcohol consumption is a major risk factor for the development of liver steatosis, fibrosis, and cirrhosis, but the mechanisms by which alcohol causes liver damage remain incompletely elucidated. This group has reported that α4 nicotinic acetylcholine receptors (α4 nAChRs) act as sensors for alcohol in lung cells. This study tested the hypothesis that α4 nAChRs mediate the effects of alcohol in the liver. Methods: Expression of acetylcholine receptor subunits in mouse liver was determined by RNA sequencing (RNA‐seq). α4 nAChR knockout (α4 KO) mice were generated in C57BL/6J mice by introducing a mutation encoding an early stop codon in exon 4 of Chrna4, the gene encoding the α4 subunit of the nAChR. The presence of the inactivating mutation was established by polymerase chain reaction and genomic sequencing, and the lack of α4 nAChR function was confirmed in primary fibroblasts isolated from the α4 KO mice. Wild‐type (WT) and α4 KO mice were fed the Lieber‐DeCarli diet (with 36% of calories from alcohol) or pair fed an isocaloric maltose‐dextrin control diet for a 6‐week period that included a ramping up phase of increasing dietary alcohol. Results: Chrna4 was the most abundantly expressed nAChR subunit gene in mouse livers. After 6 weeks of alcohol exposure, WT mice had elevated serum transaminases and their livers showed increased fat accumulation, decreased Sirt1 protein levels, and accumulation of markers of oxidative stress and inflammation including Cyp2E1, Nos2, Sod1, Slc7a11, TNFα, and PAI1. All these responses to alcohol were either absent or significantly attenuated in α4 KO animals. Conclusion: Together, these observations support the conclusion that activation of α4 nAChRs by alcohol or one of its metabolites is one of the initial events promoting the accumulation of excess fat and expression of inflammatory mediators. Thus, α4 nAChRs may represent viable targets for intervention in chronic alcohol‐related liver disease. Abstract : Alcohol‐related liver disease is an important healthcare challenge. Herein, we show that mice lacking α4 nicotinic acetylcholine receptors (α4 KO mice) do not develop fatty liver like wildtype mice do when fed the Lieber‐DeCarli liquid alcohol diet for 6 weeks. Although signs of inflammation, oxidative stress, and cell death were mild in this model, the α4 KO mice were protected from these effects. Therefore, α4 nicotinic acetylcholine receptors may represent viable targets for intervention in chronic alcohol‐related liver disease.